Climate Adaption for Energy Utilities: Lessons Learned From California's Pioneering Regulatory Actions - Ziaja, Sonya; Chhabra, Mohit (Frontiers in Climate, 2021)
This Policy Brief provides lessons learned from regulation of climate adaptation by energy utilities. The regulatory bodies responsible for oversight of investor-owned energy utilities are ill-equipped to regulate climate adaptation in the energy sector; but they may be the only institutions with authority to do so. In 2018, the California Public Utilities Commission initiated the first quasi-legislative procedure to regulate investor owned energy utilities' climate adaptation activities. The Commission's new rules for climate adaptation offer some general guidance on climate adaptation, and require investor owned utilities to conduct and submit climate vulnerability studies. Structural limitations, including conflicting interest, capacity of staff, and scope of the problem hampered the success of adaptation regulation, which failed to address fundamental questions about what constitutes adaptive measures.